Efeito do manejo e da adubação mineral no crescimento de Eucalyptus saligna Smith na segunda rotação - Deloss, Alisson de Mello (2021)
Soil fertility and nutrient export are important for the management of forest residues from harvesting. Nutrient exports can be higher or lower depending on the type and amount of residue left in the field. The sustainability of production and forest growth depends on numerous factors, and nutrient replacement is a practice that can minimize the impacts of nutrient export through harvesting. Therefore, this work aims to evaluate whether doses of mineral fertilization, in different waste management systems from the first rotation harvest, influence the growth and soil fertility in the second rotation of Eucalyptus saligna Smith in São Gabriel, RS. Before the harvest of the forest stand prior to the planting of Eucalyptus saligna Smith, the amount of nutrients in each component of tree biomass was determined, used to carry out additional fertilization as a way to replace 50% and 100% of the nutrients exported by the harvest of the first rotation. Thus, the experiment was conducted with the following treatments: T1- With residues + base fertilization; T2- With residues + base fertilization + cover fertilization; T3- No residues + base fertilization; T4- No residues + base fertilization + cover fertilization; T5- No residues + base fertilization + 50% of the nutrients exported by the harvest; T6- No residues + base fertilization + 100% of the nutrients exported by the harvest. The N, P and K are present in greater concentration in the leaves of the plant. Ca and Mg are present in greater concentration in the bark. Wood holds the greatest amount of N, P, K and Mg, due to the greater proportion of biomass in this component. The amount of total nutrients followed the following distribution order: Ca > N > K > Mg and P. It is possible to observe that if wood with bark is harvested, more than 70% of each of the evaluated macronutrients can be exported. The replacement of 100% of the nutrients exported by harvest resulted in greater growth of Eucalyptus saligna Smith, two years after planting in the treatment without harvest residue from the first rotation. The maintenance of harvest residues has a tendency to increase organic matter, when compared to treatments with residue removal, especially up to the 0 – 20 cm layer.